Odpowiedzi

2010-02-03T19:57:09+01:00
1.
{-2x+3y=3/*3
{3x-2y=-2/*2

-6x+9y=9
6x-4y=-4 |
_ +

5y=5/dzlimy przez 5
y=1

-2x+3*1=3
-2x= 3-3=0

x=0
y=1
spr.: -2x+3y=3
-2*0+3*1+3

2. '
a.
{-3x+y+1=3
{-y+2=-6x+4

-3x+y=3-1
-y+6x= 4-2

3x+y=2/*(-2)
6x-y=2

-6x-2y=-4
6x-y=2 |
_ +

-3y= 2/dzielimy przez -3
y= -2/3

b.
{3y+2x=1-4y+6x
{3x=y=x-3y+1

3y+2x+4y-6x=1
3x-y-x+3y=1

-4x+7y=1
2x+2y=1 / *2

-4x+7y=1
4x+4y=2 |
_ +

11y=3/ dzelimy przez 11
y= 3/11

3x=3/11/ dzielimy przez 3
x= 3/11 * 1/3=3/33= 1\11

x= 1/11
y=3/11


c.
{½y-1/3x=1/4
{y-2x=3-4y+5x

1/2y-1/3x=1/4
y-2x+4y-5x=3

1/2y-1/3x=1/4/ *(-10)
5y-7x=3

-5y-3i1/3x= 2,5
5y-7x=3 |
_ +

3i2/3x=5 i 1/2/ dzielimy przez 3 i 2/3
x= 11/2 podzielic przez 11/3
x= 11/2 * 3/11= 33/22=3/2=1 i 1/3

1/2y - 1/3*1/3=1/4
1/2y-1/9= 1/4
1/2y=1/4 + 1/9
1\2y= 13/36/ dzielimy przez 1/2
y= 13/36 *2/1= 26/36=13/18

x=1 i 1/3
y= 13/18


d.
{12x+11y=1
{22x-21y=47

a to to nie wiem xD